2022
DOI: 10.3389/fpls.2022.934515
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals a Genetic Mechanism of Salt Tolerance Germinability in Rice (Oryza sativa L.)

Abstract: Salt stress is one of the factors that limits rice production, and an important task for researchers is to cultivate rice with strong salt tolerance. In this study, 211 rice accessions were used to determine salt tolerance germinability (STG) indices and conduct a genome-wide association study (GWAS) using 36,727 SNPs. The relative germination energy (RGE), relative germination index (RGI), relative vigor index (RVI), relative mean germination time (RMGT), relative shoot length (RSL), and relative root length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In this study, we identified a total of 17 QTLs related to four STG indices. These indices have been successfully used in previous studies on salt tolerance at the rice germination stage (Shi et al, 2017; Yu et al, 2018; Li et al, 2022). Although eight QTLs harboured previously reported genes, these genes (except AGO2 and WRKY53 ) were not reported to be involved in STG or salt stress response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we identified a total of 17 QTLs related to four STG indices. These indices have been successfully used in previous studies on salt tolerance at the rice germination stage (Shi et al, 2017; Yu et al, 2018; Li et al, 2022). Although eight QTLs harboured previously reported genes, these genes (except AGO2 and WRKY53 ) were not reported to be involved in STG or salt stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The germination rate (GR) was counted on the 10th day, and five plant replicates were randomly selected to measure shoot length (SL) and root length (RL). Relative values were calculated by dividing the value under salt treatment by that of the control (Li et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient seed germination under salt stress is a crucial prerequisite for seedling establishment and subsequent crop production in saline land, and is a quantitative trait regulated by multiple genes ( Shi et al., 2017 ; Li et al., 2022 ). In this study, we conducted GWAS to investigate the genetic basis of seed germination under salt stress utilizing a set of 541 rice varieties collected worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately measure seed germination in such a manner, we did the germination experiments on water- or NaCl solution-immersed filter paper in petri dishes (with a cover, but without seal), and refreshed the solutions in every two days. After counting germinated seeds, germination rate and germination index were calculated to evaluate seed germination status under salt stress ( Shi et al., 2017 ; Ju et al., 2022 ; Li et al., 2022 ; Mei et al., 2022 ; Zhan et al., 2023 ). In this study, we established germination grades (1 to 11) using the GR3, GR4 and GI ratios of salt stress condition to the control condition.…”
Section: Discussionmentioning
confidence: 99%